A New Clinical and Immunovirological Score for Predicting the Risk of Late Severe Infection in Solid Organ Transplant Recipients: The CLIV Score. (28th February 2020) - San-Juan, Rafael; Fernández-Ruiz, Mario; Ruiz-Ruigómez, María; López-Medrano, Francisco; Ruiz-Merlo, Tamara; Andrés, Amado; Loinaz, Carmelo; Len, Oscar; Azancot, María Antonieta; Montejo, Miguel; Rodriguez-Alvarez, Regino; Fortún, Jesús; et al.
Abstract: Background: We aimed at constructing a composite score based on Epstein-Barr virus DNAemia (EBVd) and simple clinical and immunological parameters to predict late severe infection (LI) beyond month 6 in solid organ transplantation (SOT) recipients. Methods: Kidney and liver transplant recipients between May 2014 and August 2016 at 4 participating centers were included. Serum immunoglobulins and complement factors, peripheral blood lymphocyte subpopulations, and whole blood EBVd were determined at months 1, 3, and 6. Cox regression analyses were performed to generate a weighted score for the prediction of LI. Results: Overall, 309 SOT recipients were followed-up for a median of 1000 days from transplant (interquartile range, 822–1124). Late severe infection occurred in 104 patients (33.6%). The CLIV Score consisted of the following variables at month 6: high-level EBVd (>1500 IU/mL) and recurrent infection during the previous months (6 points); recipient age ≥70 years and chronic graft dysfunction (5 points); cytomegalovirus mismatch (4 points); and CD8+ T-cell count <400 cells/μL (2 points). The area under receiver operating characteristics curve was 0.77 (95% confidence interval, 0.71–0.84). The risk of LI at day 1000 was as follows: score 0, 12.6%; score 2–5, 25.5%; score 6–9, 52.7%; score ≥10, 73.5%. Conclusions: While waiting for further external validation, the CLIV Score based on clinical and immune-virological parameters is potentially useful to stratify the risk of LI after SOT. Abstract : The CLIV Score consisted of the following variables at month 6: high-level EBVd and recurrent infection during the previous months; recipient age ≥70 years and chronic graft dysfunction; CMV mismatch; and CD8 + T-cell count <400 cells/μL.